UNDERSTANDING OF NON VERBAL BEHAVIOR CLIENTS AND TECHNIQUES IN COUNSELING SESSION - afdal, afdal (Universitas Muhammadiyah Metro, 2016)
The practice of counseling by counselor not only need the skills to understand what is expressed by the client, but were further able to understand and have skills in giving meaning to the nonverbal communication, demonstrated by the behavior of a counseling session. During this time many of counselors who focus only on what is revealed by the client and using verbal techniques alone without seeing what goes on inside the client more deeply to understand the communication indicated by nonverbal behavior. The techniques used in the discussion of this article provides the inspiration that counseling is an art, not superficial, not skeptical and just focus on one technique alone, but many of the techniques that can be used to explore client issues. Furthermore, this paper supports the philosophical theory of Gestalt who believe that the client can feel the direct presence in the counseling sessions through the practices of the techniques used, to interpret the expression of various communications made, stationing themselves and find their own meaning.